CODE-SWITCHING PATTERNS IN INFORMAL CONVERSATIONS AMONG ENGLISH EDUCATION STUDENTS - Aisyah Khairunni’mah; Natalia Arsyad; Sara A. Machmud; Muziatun Muziatun (LPPM Universitas Pahlawan Tuanku Tambusai, 2026)
This study aims to identify the types of code-switching in informal student conversations and analyze the context of its occurrence, as well as to interpret the social function behind its use. The descriptive qualitative method was used in this study, focusing on the informal conversations of English Language Education Study Program students at State University of Gorontalo. The data collected was obtained through audio recordings which were then transcribed verbatim. Analysis was conducted using code-switching theory from Poplack (1980), which categorizes three types of switching: inter-sentential, intra-sentential, and tag switching. To interpret the social function, this study applies the theoretical framework from Holmes (2013) and Wardhaugh and Fuller (2021). The findings show that intra-sentential switching is the most frequently used type of code-switching. Code-switching often occurs in certain contexts: when discussing academic topics, when expressing feelings, when emphasizing an idea, and when maintaining group solidarity. This study also found that code-switching is used naturally as part of multilingual communication in students' daily interactions.